The Influence of Entrepreneurial Characteristics, Product Innovation, and Digital Literacy on MSME Performance - Bagaskara, Akbar; Pramesti, Diesyana Ajeng (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the influence of Entrepreneurial Characteristics, Product Innovation, and Digital Literacy on the performance of MSMEs in Magelang City and Regency. This study used a quantitative approach with a purposive sampling technique, involving 102 respondents, namely MSMEs that had been operating for at least two years. Data were collected through a questionnaire using a 5-point Likert scale and then analyzed using multiple linear regression with SPSS 25 software. The results showed that Product Innovation and Digital Literacy had a positive and significant influence on MSME performance, while Entrepreneurial Characteristics had no significant influence on MSME performance. These findings emphasize the importance of strengthening product innovation and digital literacy to improve MSME performance in an era of increasingly fierce business competition